Palermo, Hernán, Cadenas de oro negro en el esplendor y ocaso de YPF - Jaime Guiamet (H-Industri@)
Palermo, Hernán, Cadenas de oro negro en el esplendor y ocaso de YPF, Buenos Aires, Antropofagia, 2012 (292 págs.), ISBN 978-987-1238-90-3.